Impact of Unemployment, Social Protection Spending, and SMEs on the Underprivileged Population Number - Novia Ruth Silaen; Emmelia Arihta Ginting; Dearma Sariani Sinaga (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the effect of unemployment, realization of social protection costs, and Regency/City Minimum Wages (UMK) on the number of poor people in 23 regencies/cities in North Sumatra Province in the period 2020–2024. The approach used is quantitative with secondary data from BPS and DJPK, as well as panel data regression analysis using the EViews 9 application. The best estimation model chosen is fixed effect. The results of the study show that unemployment has a positive and significant effect on poverty, which means that the higher the unemployment, the higher the poverty rate. Conversely, the realization of social protection costs and UMK have a negative and significant effect, which means that an increase in these two variables can reduce the number of poor people. These findings emphasize the importance of effective social protection policies and UMK adjustments as a strategy to reduce poverty in the regions, as well as improve people's welfare